Physical Therapy 2.0: Leveraging Social Media to Engage Patients in Rehabilitation and Health Promotion. Issue 3 (1st March 2015) - Knight, Emily; Werstine, Robert J.; Rasmussen-Pennington, Diane M.; Fitzsimmons, Deborah; Petrella, Robert J.
Abstract : Care for chronic conditions and noncommunicable diseases is dominating health systems around the globe. For physical therapists, this strain presents a substantial opportunity for engaging patients in health promotion and disease management in the years to come. Examples of social media being used to engage consumers in the business landscape are pervasive, and research reports suggest that patients are ready for social media to be incorporated into the way health care systems deliver care. We propose that leveraging the power and utility of existing technologies, such as social media, could innovate the way physical therapists engage patients in rehabilitation and health promotion practices, thus contributing to the evolution of the profession: Physical Therapy 2.0. To continue to be relevant in the community, physical therapist practice must respond to patients' needs and expectations. Incorporating social media into how physical therapists are both designing and delivering care holds potential for enhancing patient engagement in prescribed health behaviors and improving treatment outcomes. This conceptual article presents the perspective that physical therapists can utilize social media to enhance care delivery and treatment outcomes.